(untitled) - Turnbull, C. M. (Singapore, 1989)
The first edition narrated Singapore history up to 1975: this new edition brings the story up to the elections of 1988. The period after 1975 saw consolidation and steady progress, during which the Singapore Republic has been one of the most stable and prosperous countries in Asia. A clearer picture of the nation and its government now emerges, and it is possible to begin to look at Singapore society as a whole.
Keywords: Singapore,Singapore; Lịch sử,History